(3JdNjU cJGH LGdjfhS aj Gdbhi GdWHjYjIs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3Ydi Hf GHQGgje Hf CMeO GdJLjHi s)
(3ChdgG (B:s
(3bGd(B: (3Efg deG cGf gG gfG aYdGf NGUGf HGdMjhGf hgeG GdMS hGdMQcI GdEQGOjI ai GdecGf , haYdGf eTJQcGf dfHGJ hGdMjhGf hgeG GdJZPj hGdfeh, SejJ GdbhI GdJi jUOQ YfgG hGdMcI GdEQGOjI faSgG s
(3BNQgG (B:s
(3ced JdNjU GdKdGK ebdGJ ef cJGH Gdbhi GdWHjYjI dLGdjfhS s
(3GdfSNI HgG MhGTs
(3GfXQ eY JdNjU cJGH GdMejGJ Qbe (B"423"s
(3HOGjI cJGHJgG ef (B634 - 637(3g`s
(3Cced fSNgG Ydj Hf GHQGgje Hf CMeO GdJLjHj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B68 s
Keywords: (3GdWHs